2007
DOI: 10.1097/ico.0b013e318030df5a
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Progressive Keratoconus by Riboflavin-UVA-Induced Cross-Linking of Corneal Collagen

Abstract: Reduction in anterior and intermediate stromal keratocytes followed by gradual repopulation has been confirmed directly in vivo in humans by HRT II-RCM confocal microscopy after riboflavin-UVA-induced corneal collagen cross-linking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
105
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(119 citation statements)
references
References 19 publications
8
105
0
6
Order By: Relevance
“…Because we had also investigated corneal sensitivity in our patients pre- and postoperatively, and because sensitivity was clearly reduced in all patients after treatment compared with preoperative baseline findings, it is likely that the subbasal nerve plexus in the treated area is destroyed as a result of therapy. The research team led by Mazzotta also arrived at this conclusion [34]. Nevertheless, it is still unclear whether complete nerve fiber destruction occurs as a result of mechanical epithelial abrasion and of riboflavin/UVA treatment, or whether the nerve plexus simply cannot be visualized on confocal microscopy during the initial postoperative months.…”
Section: Discussionmentioning
confidence: 98%
“…Because we had also investigated corneal sensitivity in our patients pre- and postoperatively, and because sensitivity was clearly reduced in all patients after treatment compared with preoperative baseline findings, it is likely that the subbasal nerve plexus in the treated area is destroyed as a result of therapy. The research team led by Mazzotta also arrived at this conclusion [34]. Nevertheless, it is still unclear whether complete nerve fiber destruction occurs as a result of mechanical epithelial abrasion and of riboflavin/UVA treatment, or whether the nerve plexus simply cannot be visualized on confocal microscopy during the initial postoperative months.…”
Section: Discussionmentioning
confidence: 98%
“…Both objective (14,15) and subjective (16) improvements were reported in eyes with keratoconus after CXL treatment, even in subjects under 18 (17). As collagen bonds are established at a depth of 250-350 µm in the anterior stroma, called the treatment zone (5,(18)(19)(20)(21), and for the protection of the endothelium, a minimum of 400 µm stromal thickness is suggested (5,22). However, according to other publications, a minimum of 330 µm of initial thickness is also sufficient for CXL after corneal swelling (23).…”
Section: Discussionmentioning
confidence: 99%
“…In the older Group, reduction in thinnest pachymetry was lesser in magnitude (mean change −38.72 µm, p < 0.0001; and −31.0 µm, p < 0.0001 at three and six months respectively) but statistically significant. This reduction in thinnest pachymetry can be attributed to measurement artifact as it has been shown that optical pachymetry is affected negatively by the non-homogen- ous optical changes seen in crosslinked corneas (due to corneal haze/demarcation line/stromal edema) [23] [24]. The Siena Study group [17] compared pachymetric results of the optical Obrscan IIz with ultrasound pachymetry and confocal pachymetric examinations and found a significant underestimation (−120 µm in the first six months) of corneal thickness with the Orbscan IIz.…”
Section: Discussionmentioning
confidence: 99%